AHOK: SIMBOL ANOMALI BAHASA KELAS PENGUASA - Mulyadi Mulyadi (OKARA: Jurnal Bahasa dan Sastra, 2016)
One of the distinguishing features between the ruling class with the lower class is language. The higher stratum of someone then he has a tendency to use the language as well as, as smooth as, or as a good order as possible. But this credo does not apply to Basuki Tjahaja Purnama called  Ahok, as Head of Jakarta region,  he communicates in a language far from polite, smooth, and well,  sometime he uses rough language, gratuitous, even invective. Ahok selected to be analyzed because in the social fact Ahok is deemed to have a behavior that is controversial that reveals the good government jargon without corruption and nepotism with languages that are far from a good order of language used by the elits. This article tries to analyze and compare the language of politics that used by Ahok that represent the ruling class of the ruling in a metropolis and became the capital of the State in the reform era (freedom) with the language used in the era of Soeharto.